2004
DOI: 10.1007/bf03018554
|View full text |Cite
|
Sign up to set email alerts
|

Recurrent cytomegalovirus disease, visceral leishmaniosis, and Legionella pneumonia after liver transplantation: a case report

Abstract: P Pu ur rp po os se e: : Recurrent cytomegalovirus (CMV) disease is a frequent complication of liver transplantation. Visceral leishmaniosis in a transplant recipient is, on the other hand, extremely rare and only two cases of kala-azar have been described after liver transplantation. Immunosuppressed patients are known to be at risk of Legionella infection and the relationship between infection with this organism and hospital water supplies has been well described. These three diseases carry a high mortality … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
20
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 12 publications
1
20
0
Order By: Relevance
“…On the other hand, VL is being reported with increasing frequency in transplant recipients, with 80 cases reported thus far (4, 7), while the originally high risk for HIV-infected patients appears to be greatly reduced since the turn of the century, thanks to immune reconstitution mediated by effective antiretroviral treatments. The most likely pathogenetic mechanisms of VL in transplant patients are either primary infection acquired by immunosuppressed subjects traveling in regions of endemicity (27) or reactivation of a preexisting asymptomatic infection in the recipient (5), while iatrogenic acquisition through either an infected graft or blood transfusion probably represents an uncommon situation. In fact, only 12 posttransfusion VL cases have been reported, to our knowledge, since 1948 (15, 43); 11 of the above occurred in infants or children, who are highly receptive to Leishmania, while the relevance of blood transfusion in the immunocompetent adult host is controversial (8).…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, VL is being reported with increasing frequency in transplant recipients, with 80 cases reported thus far (4, 7), while the originally high risk for HIV-infected patients appears to be greatly reduced since the turn of the century, thanks to immune reconstitution mediated by effective antiretroviral treatments. The most likely pathogenetic mechanisms of VL in transplant patients are either primary infection acquired by immunosuppressed subjects traveling in regions of endemicity (27) or reactivation of a preexisting asymptomatic infection in the recipient (5), while iatrogenic acquisition through either an infected graft or blood transfusion probably represents an uncommon situation. In fact, only 12 posttransfusion VL cases have been reported, to our knowledge, since 1948 (15, 43); 11 of the above occurred in infants or children, who are highly receptive to Leishmania, while the relevance of blood transfusion in the immunocompetent adult host is controversial (8).…”
Section: Discussionmentioning
confidence: 99%
“…In this review, all of the infected patients, except one, were seropositive at the time of diagnosis of VL. This suggests that, at least in active infection, serological testing has a high diagnostic sensitivity similar to that found in other patient populations, with the exception of HIV‐infected patients, among whom sensitivity is lower than 50% 2, 6, 12. It should be taken into account that serology may test positive in individuals from endemic areas because of past exposure in the absence of active infection 17.…”
Section: Discussionmentioning
confidence: 55%
“…Remarkably, very few cases have been described among liver transplant recipients. We report a case of VL in a liver transplant recipient and analyze the other 9 cases published in the literature 3–9…”
mentioning
confidence: 99%
“…9,10 Halkic et al 11 suggested that opportunistic CMV infections with a high viral load, as encountered by our patient, may additively trigger leishmaniasis in patients from endemic area's with latent infections. However, VL and CMV reactivation in the present patient can both be caused by the same conditions brought about by the deep lymphopenia.…”
mentioning
confidence: 59%